1996
DOI: 10.1111/j.1532-849x.1996.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Esthetics: Patients' Perceptions of Dental Attractiveness

Abstract: In all cases, tooth shade was the most important factor, followed in sequence by unrestored natural teeth and number of teeth displayed. No correlation was found to exist between specific demographic groups and smile variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
1
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 23 publications
10
74
1
7
Order By: Relevance
“…Unlike these findings and agreeing with Dunn et al, 20 the results of this study demonstrated that varying buccal corridor widths significantly affected smile attractiveness. This influence was not affected by gender, coinciding with the findings of Moore et al, 14 nor by ethnicity, as shown in Tables 1 and 2.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Unlike these findings and agreeing with Dunn et al, 20 the results of this study demonstrated that varying buccal corridor widths significantly affected smile attractiveness. This influence was not affected by gender, coinciding with the findings of Moore et al, 14 nor by ethnicity, as shown in Tables 1 and 2.…”
Section: Discussioncontrasting
confidence: 57%
“…This result was similar to the one found by Gracco et al, 4 who detected a preference for an image with buccal corridor equivalent to 18.46% of the width of the smile, and disagreed with Moore et al, 14 who reported as more attractive a smile with a lateral negative space of 2%. Such difference may have occurred as a result of the fact that in the study by Moore et al, 20 the buccal corridor was measured based on inner commissures. Moreover, their method for changing the variable was different, i.e., the intercanine width was maintained while the number and width of the posterior teeth were modified.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Few articles relate to their clinical use 14,[16][17] or conduct studies with larger samplings. 15,19,[22][23] Thus, some of the esthetic principles were applied using an objective analysis in a sample of 100 patients to verify their applicability.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a survey conducted in New Zealand, most participants reported an increased demand for tooth-whitening (77.8%) and veneers (54.8%) subsequent to the broadcasting of television programs promoting dental esthetics. 4 It has been reported, in a study of patients' perceptions of dental attractiveness, that one of the most important considerations in judging the attractiveness of a finished dental restoration is its shade, 5 which constituted 77% of the smile attractiveness variables for men and 61% for women; other variables, such as natural teeth, display, symmetry, and lip line, constituted the remaining 23% for men and 39% for women. 5 It has also been reported that any difference in the shade of the restoration compared with that of the natural tooth must be perceptible to the patient to be important.…”
Section: Introductionmentioning
confidence: 99%